Establishment and optimization of a system for the detection of Candida albicans based on enzymatic recombinase amplification and CRISPR/Cas12a system - Xiaotong Zeng; Qiuyang Jiang; Fo Yang; Qianlin Wu; Tingyao lyu; Qi Zhang; Jin Wang; Feng Li; Dayong Xu (Microbiology Spectrum)
ABSTRACT Invasive candidiasis is a fungal infection caused by various pathogenic yeasts, with Candida albicans as the predominant pathogen. Traditional culturing and identification methods for C. albicans are slow, requiring several days to weeks to produce results, which hampers rapid diagnosis. In this study, we proposed three amplification methods to combine with CRISPR/Cas12a and selected the enzymatic recombinase amplification (ERA) and CRISPR/Cas12a two-step method for the detection of C. albicans in terms of sensitivity, and then the two-step method was optimized to a temperature-controlled one-step method for the detection of C. albicans by enzymatic recombinase amplification (ERA)-CRISPR/Cas12a. The temperature-controlled system employs a combination of liquid and solid paraffin wax to maintain the desired melting point, thus facilitating spatial separation of the ERA amplification system from the CRISPR/Cas12a detection system within a single tube. After a reaction at 37°C, the temperature is raised to 45°C, melting the wax and allowing the amplification system to merge with the detection system, initiating the reaction. This one-step detection platform simplifies and expedites the procedure, achieving a sensitivity level on par with that of two-step methods. The reaction completes in about 30 minutes, detecting as little as 100 ag/µL of genomic DNA from C. albicans pure cultures. It shows high specificity and resistance to clinical nucleic acid interference, without cross-reactivity. Additionally, the method eliminates the need to open the reaction tube, effectively preventing aerosol contamination and providing a stable, thus offering a new tool for the rapid clinical diagnosis of C. albicans.IMPORTANCEThis study established a two-step method through optimization, compared its sensitivity, and then combined the specific detection capabilities of ERA and CRISPR/Cas12a. Furthermore, a one-step method was developed based on the two-step method, creating a one-step system for the detection of Candida albicans. This system does not require the lid to be opened during the reaction process, reducing aerosol contamination and minimizing the risk of false positives. This method does not require advanced instruments or equipment and shows strong specificity without being affected by other pathogens. It can serve as a new method for the detection of Candida albicans and has significant practical application prospects.